CRISPR-Cas System, a Possible “Savior” of Rice Threatened by Climate Change: An Updated Review - Nabeel Shaheen; Shakeel Ahmad; Salem S Alghamdi; Hafiz Mamoon Rehman; Muhammad Arshad Javed; Javaria Tabassum; Gaoneng Shao (Rice, 2023)
Abstract Climate change has significantly affected agriculture production, particularly the rice crop that is consumed by almost half of the world’s population and contributes significantly to global food security. Rice is vulnerable to several abiotic and biotic stresses such as drought, heat, salinity, heavy metals, rice blast, and bacterial blight that cause huge yield losses in rice, thus threatening food security worldwide. In this regard, several plant breeding and biotechnological techniques have been used to raise such rice varieties that could tackle climate changes. Nowadays, gene editing (GE) technology has revolutionized crop improvement. Among GE technology, CRISPR/Cas (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein) system has emerged as one of the most convenient, robust, cost-effective, and less labor-intensive system due to which it has got more popularity among plant researchers, especially rice breeders and geneticists. Since 2013 (the year of first application of CRISPR/Cas-based GE system in rice), several trait-specific climate-resilient rice lines have been developed using CRISPR/Cas-based GE tools. Earlier, several reports have been published confirming the successful application of GE tools for rice improvement. However, this review particularly aims to provide an updated and well-synthesized brief discussion based on the recent studies (from 2020 to present) on the applications of GE tools, particularly CRISPR-based systems for developing CRISPR rice to tackle the current alarming situation of climate change, worldwide. Moreover, potential limitations and technical bottlenecks in the development of CRISPR rice, and prospects are also discussed.